Effect of overnight soaking and boiling on phytic acid, tannins, saponins and proximate composition in legumes - Qureshi, Samawia; Hamid, Asmaa (Journal of Pure and Applied Agriculture, 2023)
The nutritional value of legumes depends not only on the nutrients but also on anti-nutrients that hinder their absorption. Simple domestic cooking procedures can greatly influence nutrients and anti-nutrients in legumes. The overnight soaking (in tap water, 0.9% w/v NaHCO3 solution and 1.5% w/v vinegar solution) prior to boiling among three legumes was studied; red kidney beans (Phaseolus vulgaris), chickpeas (Cicer arietinum) and bengal grams (Cicer arietinum) which significantly (p <.001) reduced phytic acid, tannins, saponins and ash content, whereas, crude protein, crude fiber and carbohydrates increased significantly (p <.001), enhancing the nutritional quality of legumes. The most drastic reduction of phytic acid (33.07% in red kidney beans, 41.13% in chickpeas and 40.47% in bengal grams) was observed after boiling the overnight soaked legumes in